Effectiveness of non-pharmacological interventions for managing agitation during post-traumatic amnesia following traumatic brain injury: a systematic review protocol. Issue 2 (5th February 2021) - Carrier, Sarah L.; Hicks, Amelia J.; Ponsford, Jennie L.; McKay, Adam
ABSTRACT: Objective: To synthesize current evidence on the effects and harms of non-pharmacological interventions for managing agitation during post-traumatic amnesia in adults who have sustained a traumatic brain injury. Introduction: Agitation is one of the most disruptive and clinically significant sequelae observed during post-traumatic amnesia. Patients who experience agitation during this period demonstrate reduced engagement in rehabilitation and poorer long-term functional outcomes. Agitation also poses a risk to staff and patient safety. Research for the effects of pharmacological intervention for managing agitation during this period is inconclusive. Thus, synthesis of the research for non-pharmacological interventions for reducing agitation during post-traumatic amnesia is essential for improving long-term outcomes for survivors of traumatic brain injury. Inclusion criteria: Studies will be considered if they include participants aged 16 years and older who exhibit agitated behaviors during post-traumatic amnesia after sustaining a traumatic brain injury (irrespective of severity or mechanism). Studies will be considered if they evaluate any non-pharmacological intervention for reducing agitation, with all types of comparators accepted. Primary outcomes of interest include a change in agitation severity and any adverse effects. Methods: Key information sources include MEDLINE Ovid SP interface, PubMed, CINAHL, Excerpta Medica Database, PsycINFO, and Cochrane CENTRAL. Studies published in English will be included, irrespective of publication year. Two independent reviewers will be involved in study selection and data extraction. Eligible studies will be critically appraised for methodological quality. Studies will be pooled with statistical meta-analysis where possible; otherwise findings will be reported in narrative form. Systematic review registration number: PROSPERO CRD42020186802